Implementation of ANFIS in Forecasting the Development of Renewable Energy in Indonesia in 2027 - Yoga Tri Nugraha; Kelvin Ghabriel; Syahrun Nizam Md Arshad (ETAPs (Journal Electronics, Telecommunication, Electrical, and Physics Science, 2021)
An important energy fuel for power generation is utilizing petroleum products such as oil and coal. The use of basic fuels is increasing every year and the main fuel reserves are getting depleted/decreasing. In driving a generator, alternative energy is needed whose sources will not run out and can reduce the use of petroleum derivatives. This source is new and renewable energy. To ensure the development of new and renewable energy, it is important to forecast the development of new and renewable energy in Indonesia in 2027 using ANFIS. The results obtained in predicting the development of new and renewable energy in Indonesia in 2027 are 990,94 MW.